PENGARUH CAPITAL STRUCTURE, LIQUIDTY, EARNING PER SHARE DAN PROFITABILTY TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2017 - Elfrida Pakpahan; Annisa Nauli Sinaga; Jaka Permana (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The purpose of this study is to examine and analyze the influence of variables of capital structure, liquidity, earning per share, and profitability on the value of the company in the manufacturing company listed in Indonesia Stock Exchange in the period of 2014-2017. This study used secondary data taken by documentation method that is the company’s annual financial report 2014-2017. This research used quantitative approach and the 52 sampels were drawn using purposive sampling technique out of 152 company data that me criteria. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that partially, capital structure, liquidity, and earning per share has no significant effect on the firm value. Simultaneously, profitability have a significant effect on firm value of the company companies of manufacturing companies listed on the Indonesia Stock Exchange in the period of 2014-2017.